ANALISIS PERBEDAAN KUALITAS ACCRUAL ANTARA SEBELUM DAN SESUDAH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARD (IFRS) PADA PERUSAHAAN MANUFAKTUR DI INDONESIA(Studi Empiris pada Perusahaan Manufaktur yang terdapat di Bursa Efek Indonesia Tahun 2009-2014) - Windarti, Esti; Sasongko, Noer; Zulfikar, Zulfikar (Universitas Muhammadiyah Surakarta, 2017)
The purpose of this study to examine the numbers between the accrual quality difference before and after adopting International Financial Reporting Standards (IFRS). The population in this study are all manufacturing companies listed in Indonesia Stock Exchange 2009-2014. Sampling using purposive sampling selection of samples with specific criteria.Analysis of the data used is by using normality test and analysis methods paired sample t-test. Calculation of accruals quality using the 2 models that Dechow and Dichev Model and Modified Jones Models. From the test results showed that there was a difference in quality between the accrual before and after adopting International Financial Reporting Standard (IFRS) for 2009-2014 by using Dechow and Dichev Model, while contrary to the results of testing using the Modified Jones Model. The difference is due to the result of the absence of a change in accounting rules and the transition period that occurred in Indonesia.Â Keywords: Quality acrual , International Financial Reporting Standard ( IFRS ), Manufacturing Company , Paired Sample T -test